Pendampingan Pembuatan Kipas Lukis Aklirik di Madrasah Diniyah Miftahul Huda Ponorogo - Azhari, Adelia Novita; Widyaningrum, Heny Kusuma; Lukitasari, Diah Ayu; Fathullah, Fahrul Abawain; Sulistiowati, Hera; Mahaningrum, Irla Fetriana; Putri, Indah Wigati; Khusna, Isa Asmaul; Sodik, Jafar; Jati, Kenang Ageng; Madi Pratama, Heny Danniy (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to 1) introduce madrasah students to the process of making bamboo fans, 2) introduce efforts that can be made to improve the aesthetic value of bamboo fans, and 3) facilitate children's creativity through bamboo fan coloring activities. This activity is motivated by the importance of developing creativity as an essential skill that aligns with the madrasah's efforts to adapt to the times. The method used is a participatory project approach involving preparation, implementation, and evaluation stages conducted through interviews. The results of the community service demonstrated high enthusiasm and engagement from the participants, as well as positive appreciation from the madrasah, which considered the sustainability of similar activities. The contribution of this community service to knowledge, particularly in the field of education, lies in demonstrating an innovative model of extracurricular activities utilizing local resources. Additionally, the activity provided practical knowledge regarding the implementation of project-based learning in the context of madrasah diniyah and its potential to enrich the repertoire of adaptive teaching methods tailored to students' needs and the environment.